An economic analysis of the carnation industry in the United States - Besemer, Seward Thayer, author (Colorado State University. Libraries, 1966)
An economic analysis of the carnation industry in the United States was conducted by mail questionnaires surveying growers, shippers, and wholesalers. Production costs, total revenues, investments, types of greenhouses, methods of financing, plant densities, flower yields, management and other cultural problems, and climatic factors were determined for seven production areas. Western production areas, such as California and Colorado were shown to have the advantages of higher production, producing at relatively less cost per unit, and capabilities of supplying all national markets by fast air and truck freight. Older established eastern areas were shown to be stabilizing or decreasing carnation production because of western area competitive advantages and improved transportation. A general flow pattern of carnations during seasons of the year was determined between production areas and market areas. The western production areas supply the main volume of carnations sold in all sections of the country, except the Northeast. Shipping prices and wholesale market prices were shown to vary with geographical region, being somewhat lower on the west coast and in the New York area. Essentially, carnation prices appear to be quite stable, there being a winter and spring price and a lower summer price. Problems of the industry, as reported by participants in the survey are many. Predominating was the need for uniform, grading, more consistent supply, less transportation delays, better handling and less storage of flowers for holidays. The need for more economic information for management decision making was emphasized.
Keywords: Carnations; Floriculture